Characterization of the hepatic cytochrome P450 enzymes involved in the metabolism of 25I‐NBOMe and 25I‐NBOH. Issue 5 (12th July 2016) - Nielsen, Line Marie; Holm, Niels Bjerre; Leth‐Petersen, Sebastian; Kristensen, Jesper Langgaard; Olsen, Lars; Linnet, Kristian
Abstract : The dimethoxyphenyl‐N‐((2‐methoxyphenyl)methyl)ethanamine (NBOMe) compounds are potent serotonin 5‐HT2A receptor agonists and have recently been subject to recreational use due to their hallucinogenic effects. Use of NBOMe compounds has been known since 2011, and several non‐fatal and fatal intoxication cases have been reported in the scientific literature. The aim of this study was to determine the importance of the different cytochrome P450 enzymes (CYP) involved in the metabolism of 2‐(4‐iodo‐2, 5‐dimethoxyphenyl)‐N‐(2methoxybenzyl)ethanamine (25I‐NBOMe) and 2‐[[2‐(4‐iodo‐2, 5dimethoxyphenyl)ethylamino]methyl]phenol (25I‐NBOH) and to characterize the metabolites. The following approaches were used to identify the main enzymes involved in primary metabolism: incubation with a panel of CYP and monoamine oxidase (MAO) enzymes and incubation in pooled human liver microsomes (HLM) with and without specific CYP chemical inhibitors. The study was further substantiated by an evaluation of 25I‐NBOMe and 25I‐NBOH metabolism in single donor HLM. The metabolism pathways of 25I‐NBOMe and 25I‐NBOH were NADPHdependent with intrinsic clearance values of (CLint) of 70.1 and 118.7 mL/min/kg, respectively. The biotransformations included hydroxylation, O‐demethylation, N‐dealkylation, dehydrogenation, and combinations thereof. The most abundant metabolites were all identified by retention time and spectrum matching with synthesized reference standards. The major CYP enzymes involved in the metabolism of 25I‐NBOMe and 25INBOH were identified as CYP3A4 and CYP2D6, respectively. The compound 25I‐NBOH was also liable to direct glucuronidation, which may diminish the impact of CYP2D6 genetic polymorphism. Users of 25I‐NBOMe may be subject to drug‐drug interactions (DDI) if 25I‐NBOMe is taken with a strong CYP3A4 inhibitor. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The aim of this study was to determine the importance of the different cytochrome P450 enzymes involved in the metabolism of designer drugs 25I‐NBOMe and 25I‐NBOH and contribute to characterization of metabolites. The major CYP enzymes involved in the metabolism of 25I‐NBOMe and 25INBOH were identified as CYP3A4 and CYP2D6, respectively, based on recombinant CYP enzymes and HLM incubations.